Strategic Digital Communication for Empowering Online Communities: A Case Study of Youtz Community Hub - Fathiyyah Azizah; Martha Tri Lestari (Jurnal the Messenger, 2025)
Purpose: This study aims to analyze communication strategies in empowering online communities for the development of digital social innovation through Youtz Community Hub. This study was conducted to determine how communication strategies can support community empowerment and encourage the creation of social innovation in the digital era.